Bacterial Flora associated with Penaeus monodon hatchery system. - Villaflor, Ma. Louella Gemarino (1996.)
A study was carried out to identify the microflora of larvae, post-larva of prawn and in their rearing waters and feeds through their morphological and biochemical characteristics. Six generic groups were identified: Vibrio spp., Pseudomonas sp., Escherichia spp., Moraxella spp., Micrococcus spp., "coryneforms" Vibrio spp. is the dominant genus identified among the isolates. Water isolates has more types of bacterial flora present. Contaminated water could be a source of infection in hatchery systems.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Penaeus Monodon